The Role of Behavioral Finance in Understanding Market Anomalies - Arya, Dr. Sandeep; Singh, Dr. Shekhar (South Eastern European Journal of Public Health, 2025)
Behavioral finance has emerged as a critical field in understanding market anomalies that traditional financial theories struggle to explain. This paper delves into the role of behavioral finance in identifying and interpreting irregularities in financial markets, such as bubbles, crashes, and deviations from expected market efficiency. Drawing upon key concepts, including cognitive biases, emotional influences, and heuristics, the study explores how these psychological factors impact investor behavior and decision-making. The paper emphasizes the limitations of the Efficient Market Hypothesis (EMH), which assumes rational behavior and market efficiency, by highlighting real-world evidence of irrational market phenomena. It discusses pivotal behavioral finance theories, such as prospect theory, mental accounting, and herd behavior, which provide a framework for understanding why investors often deviate from rationality. The review further investigates the implications of these theories in addressing anomalies such as momentum, overreaction, and underreaction in asset pricing. Additionally, the role of behavioral finance in shaping regulatory policies and investment strategies is examined, showcasing its potential in mitigating risks and improving market stability. Emerging trends in behavioral finance, including the integration of artificial intelligence and big data analytics to better predict investor sentiment, are also explored. The findings underscore the necessity of incorporating behavioral finance insights into financial education, policy-making, and investment practices to foster more resilient and efficient markets. By offering a comprehensive understanding of the psychological drivers behind market anomalies, this paper contributes to the growing body of literature that bridges the gap between traditional finance and behavioral science. This paper aims to provide valuable perspectives for academics, practitioners, and policymakers, encouraging a deeper appreciation of behavioral finance as a transformative lens for analyzing financial markets.